Roles and Responsibilities Land Deed Official (PPAT) Of Tax Duty in the Implementation of Acquisition of Land and Buildings (BPHTB) Underpayment by the Taxpayers in Semarang - Ahmad Khalimaya Nugroho; Insan Al Ha Za Zuna Darma Illahi; Sri Endah Wahyuningsih (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this research are: 1) To identify and analyze the role of responsibility in the Land Deed Official BPHTB implementation of extant underpayment by the taxpayer in the city of Semarang. 2) To know and understand the procedures for implementing the tax collection of BPHTB the underpayment by the taxpayer in the city of Semarang. 3) To analyze the barriers and solutions in tax collection is less paid by the taxpayer in the city of Semarang.The methods of this research approach is empirical jurisdiction. Primary data was taken by the method of structured interviews, secondary data, and the data tertiary literature study and analysis by descriptive analytical method.Based on the results of data analysis concluded that: 1) The role and responsibilities of PPAT can vary in terms of solving problems regarding the lack of pay taxes BPHTB, first there are some of PPAT to omit some chapters in a deed of them, and some are not stated with a settlement notice or in the form of an appeal as officials land deed to the client or taxpayers.2) procession conducted by the tax authorities namely Apparatus State Civil circulate bills of underpayment of tax is intended to taxpayers who are still their underpayment of tax by nature force because the circulars issued by phisicus accordance with rule and regulations in force in accordance with Regulation Semarang City No. 2 of 2011 Chapter VII Article 15 paragraph 1 and 2. 3) Barriers often happens is that first were often there is an error in the calculation of the nominal value of the deposit amount of tax to be paid by the taxpayer to the local government, the second presence at the crux on the amount of tax rates provided to the taxpayer by the SPPTPBB both rural and urban, as well as the steps being taken are in accordance with agreed procedures, but it is still the amount of load that must be paid by the taxpayer. The solution to these problems that is better than the Land Deed Official should conduct socialization to the client then later if there is any underpayment of tax.Keywords: Empirical Juridical Review; Pay less Tax; Customs Tax Collection Procession Acquisition of Land